CRITICAL ASSESSMENT OF LABORATORY TECHNICIANS’ CONTRIBUTIONS TO CLINICAL TESTING AND RESEARCH - 1Safar Mohammed A Alqahtani, 2Sultan Abdullah Hussain Alqahtani, 3Fahad Yahya Mohammed Asiri, 4Ali Salman Saleh Harisi, 5Salman saeed Salem Harisi, 6Ali Hassan AmerHarisi, 7Naji Aied Saleh Al Salem, 8Sultan Awad Al dalaan Al yami (Chelonian Research Foundation, 2022)
Laboratory technicians are pivotal in clinical testing and research, although their significance is frequently underestimated. This article outlines the critical role laboratory technician’s play in these areas. We highlight the importance of their commitments by looking into the information, strategies, comedies, and discourses. We recognize the challenges they confront and make proposals to make strides in their parts. We analyze our discoveries with experimental proof utilizing charts, tables, and charts. This thinks about points to make strides in collaborative care among research facility experts and clarify their imperative part in guaranteeing the keenness and precision of demonstrative and inquiry about results. Keywords: Laboratory technicians, clinical testing, research, contributions, challenges, recommendations.